1998
DOI: 10.1038/sj.bjc.6690007
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk for acute childhood lymphoblastic leukaemia in Swedish population centres 1973-94

Abstract: Summary A population-based sample of acute childhood leukaemia cases in Sweden 1973-94 was analysed by a geographical information system (GIS) for spatial leukaemia distribution in relation to population density. The annual incidence rate for acute lymphoblastic leukaemia (ALL) was 3.6, and for acute non-lymphoblastic leukaemia (ANLL) 0.7, cases per 100 000 children. Incidence rates in population centres, constituting 1.3% of Sweden's land area and approximately 80% of the population, compared with the rest of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…In contrast with previously published findings in Taiwan (Li et al, 1998), Australia (McWhirter and Bacon, 1980), Greece (Petridou et al, 1997), Sweden (Hjalmars and Gustafsson, 1999), and the United States (Muirhead, 1995), studies in the United Kingdom found higher incidence of childhood ALL in rural areas. The incidence of ALL among children aged 1 -7 years in 3270 electoral wards in England and Wales during 1984 -1988 increased over four levels of distance from built-up areas (RR ¼ 2.2; trend P ¼ 0.002) for wards 420 km from a built-up area (Alexander et al, 1990(Alexander et al, , 1996.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In contrast with previously published findings in Taiwan (Li et al, 1998), Australia (McWhirter and Bacon, 1980), Greece (Petridou et al, 1997), Sweden (Hjalmars and Gustafsson, 1999), and the United States (Muirhead, 1995), studies in the United Kingdom found higher incidence of childhood ALL in rural areas. The incidence of ALL among children aged 1 -7 years in 3270 electoral wards in England and Wales during 1984 -1988 increased over four levels of distance from built-up areas (RR ¼ 2.2; trend P ¼ 0.002) for wards 420 km from a built-up area (Alexander et al, 1990(Alexander et al, , 1996.…”
Section: Discussioncontrasting
confidence: 77%
“…Some researchers have assessed the effect of population density, as well as urbanisation per se, on incidence of ALL. Incidence of ALL among Swedish children under age 15 during 1973-1994(Hjalmars and Gustafsson, 1999 was significantly higher in 'population centres' than in the Swedish countryside (3.99 vs 2.38 cases per 100 000; OR ¼ 1.68; 95% CI ¼ 1.44 -1.95); no significant rural -urban gradient was observed for ANLL (0.67 vs 0.59 cases per 100 000; OR ¼ 1.13; 95% CI ¼ 0.98 -1.32). The childhood ALL incidence rates in Sweden increased monotonically with increasing degrees of urbanisation (3.32, 3.41, and 3.65 cases per 100 000 in 'rural', 'semiurban', and 'urban' areas, respectively), and also with increasing population density (3.55, 3.63, and 4.09 cases per 100 000 in areas with o400, 400 -800, and 4800 persons per square kilometer, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Britain have also found a higher incidence of ALL in rural or isolated areas (Alexander et al, 1990b;Dickinson and Parker, 1999). This contrasts with findings of higher incidence in urban areas in several other countries, including Greece (Petridou et al, 1997), Taiwan (Li et al, 1998), Sweden (Hjalmars et al, 1999) and the United States (Adelman et al, 2005). None of these studies controlled for socioeconomic status, however, and patterns of socioeconomic status in relation to urbanisation may differ between countries.…”
Section: Discussionmentioning
confidence: 83%
“…In a previous Swedish study, an enhanced risk of childhood ALL was found in population centres, but there was no indication that specific geographically localized areas were involved [23]. Another Swedish study on parental occupation and childhood cancer using information from the 1960 national census for occupation, showed an increased risk for lymphoma in children to seamen but no increased risk of cancer for fishermen children.…”
Section: Discussionmentioning
confidence: 98%